Characterization of Apo‐Form Selective Inhibition of Indoleamine 2, 3‐Dioxygenase. (16th November 2020) - Ortiz‐Meoz, Rodrigo F.; Wang, Liping; Matico, Rosalie; Rutkowska‐Klute, Anna; De la Rosa, Martha; Bedard, Sabrina; Midgett, Robert; Strohmer, Katrin; Thomson, Douglas; Zhang, Cunyu; Mebrahtu, Makda; Guss, Jeffrey; et al.
Abstract: Indoleamine‐2, 3‐dioxygenase 1 (IDO1) is a heme‐containing enzyme that catalyzes the rate‐limiting step in the kynurenine pathway of tryptophan (TRP) metabolism. As it is an inflammation‐induced immunoregulatory enzyme, pharmacological inhibition of IDO1 activity is currently being pursued as a potential therapeutic tool for the treatment of cancer and other disease states. As such, a detailed understanding of the mechanism of action of IDO1 inhibitors with various mechanisms of inhibition is of great interest. Comparison of an apo‐form‐binding IDO1 inhibitor (GSK5628) to the heme‐coordinating compound, epacadostat (Incyte), allows us to explore the details of the apo‐binding inhibition of IDO1. Herein, we demonstrate that GSK5628 inhibits IDO1 by competing with heme for binding to a heme‐free conformation of the enzyme (apo‐IDO1), whereas epacadostat coordinates its binding with the iron atom of the IDO1 heme cofactor. Comparison of these two compounds in cellular systems reveals a long‐lasting inhibitory effect of GSK5628, previously undescribed for other known IDO1 inhibitors. Detailed characterization of this apo‐binding mechanism for IDO1 inhibition might help design superior inhibitors or could confer a unique competitive advantage over other IDO1 inhibitors vis‐à‐vis specificity and pharmacokinetic parameters. Abstract : Inhibiting IDO1 : IDO1 is a heme‐containing tryptophan metabolizing enzyme, and identified as antitumor target. Many groups have achieved effective IDO1 inhibition. This study defines two distinct molecular mechanisms of inhibiting apo and holo forms of IDO1. The approach can serve as an example for enzyme form selective drug screening and design.